Does secondary school tracking affect performance? Evidence from IALS - Kenn Ariga; Giorgio Brunello (Institute for the Study of Labor (IZA), 2007)
There is substantial cross-country variation in secondary school design, with some countries tracking students into different ability schools very early, and other countries with little or no tracking at all. Does tracking length affects school performance, as measured by standardized test scores? We use the international data from the International Adult Literacy Survey to estimate the relationship between the experienced tracking length and the performance in standardized cognitive test scores of young adults, aged between 16 and the mid-twenties. Our IV estimates suggest that the contribution of tracking to performance is positive and statistically significant: conditional on total years of schooling, one additional year spent in a track raises average performance by 3.3 to 3.4 percentage points, depending on the estimates
urn:nbn:de:101:1-20080416197
Keywords: 330; Schulauswahl; Altersgruppe; Allgemeinbildende Schule; Bildungsniveau; Bildungschancen; Welt